War Bonnets and Calumets in the Heart of Europe: Native American Exhibition in Rosenheim, Germany: Indianer – Ureinwohner Nordamerikas. Lokschuppen. Rosenheim, Germany, April 8, 2011 – November 6, 2011 - Heřmanský, Martin (Lidé města, 2011)
This review essay focuses on representational practices of Native Americans in the exhibition Indianer – Ureinwohner Nordamerikas (Indians – Indigenous Peoples of North America) in Germany. Through an analysis of the exhibition contents, it aims to assess used representational practices and discuss how this exhibition deals with common stereotypes of Native Americans. It argues that, while the exhibition contests many common stereotypes, it also consciously or unconsciously reproduces a few others. In the conclusion it tries to find the reasons why this is so, despite the fact that the exhibition curator is one of the first anthropologists focusing on the issue of representations of Native Americans.